(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of this study was to evaluate the effect of storageperiod on weight loss, chemical composition and microbiological andsensory characteristics of white cheese (Gibna Bayda) manufactured usingSolanum dubium enzyme extract. Cheese was made (25 ml of extract /50L milk), stored for 90 days at 35°C and evaluated for weight loss,chemical composition and microbiological and sensory characteristics at1, 15, 30, 45, 60, 75 and 90 days. The results indicated that storage periodsignificantly increased weight loss and chemical components except saltcontent. Storage period had a significant effect on titratable acidity andprotein content of whey. Total viable bacteria, streptococci andlactobacilli counts (Log10 cfu/gm) decreased as the storage periodprogressed. There was a slight improvement in flavour and a decrease insaltiness, during storage, but there was no significant effect on cheesecolour and texture.